A Pilot Screening of Agro-Food Waste Products as Sources of Nutraceutical Formulations to Improve Simulated Postprandial Glycaemia and Insulinaemia in Healthy Subjects - Tenore, Gian Carlo; Caruso, Domenico; D’Avino, Maria; Buonomo, Giuseppe; Caruso, Giuseppe; Ciampaglia, Roberto; Schiano, Elisabetta; Maisto, Maria; Annunziata, Giuseppe; Novellino, Ettore (Nutrients, 2020)
The control of glucose homeostasis is the main goal for both the prevention and management of diabetes and pre-diabetes. Numerous drugs are available, despite their side effects. This is constantly leading people to be inclined to natural alternative treatments. Evidence indicates antioxidant-based nutraceuticals as an optimal tool for the glycaemic control. Currently, a great interest has been focused on the valorisation of agro-food by-products as sources of bioactive compounds including polyphenols. In this sense, we tested the efficacy of novel nutraceutical products based on polyphenolic extract from nectarines (NecP), tomato peels (TP), and olive leaves (EOL) on glycaemic and insulinemic responses. The three formulations contained, respectively, 0.007 mg abscisic acid (ABA)/g, 0.5 mg carotenoids/g, and 150 mg oleuropein/g. Twenty healthy subjects consumed a regular glucose solution (RG) or a treatment beverage (TB) obtained by mixing RG with the individual formulations (TB NecP, TB EOL, and TB TP), separately, and on different days. All three formulations significantly lowered the 30 min glucose plasma peak (p < 0.05 for all); similarly, NecP and TP also significantly lowered the 30 min insulin plasma peak (p < 0.05 for all). These results may lead to the hypothesis of a formulation of a multi-component nutraceutical with a synergistic efficacy for the glycaemic control.